2023
DOI: 10.1002/jmv.28584
|View full text |Cite
|
Sign up to set email alerts
|

Receptor‐binding domain‐based SARS‐CoV‐2 vaccine adjuvanted with cyclic di‐adenosine monophosphate enhances humoral and cellular immunity in mice

Abstract: Novel adjuvants are highly desired to improve immune responses of SARS‐CoV‐2 vaccines. This work reports the potential of the stimulator of interferon genes (STING) agonist adjuvant, the cyclic di‐adenosine monophosphate (c‐di‐AMP), in a SARS‐CoV‐2 vaccine based on the receptor binding domain (RBD). Here, mice immunized with two doses of monomeric RBD adjuvanted with c‐di‐AMP intramuscularly were found to exhibit stronger immune responses compared to mice vaccinated with RBD adjuvanted with aluminum hydroxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Irrespective of the antigen conformation, the S-specific antibodies developed in different DNA-(pCI/S, pCI/S2-P, pCI/S6-P DTM ) or proteinimmunized (S, S2-P, S6-P DTM ) young mice efficiently suppressed S-mediated cell entry of pseudovirus particles (Figure 3B). This showed that both trimeric and monomeric S proteins elicited substantial pseudovirus-neutralizing antibodies in young mice, confirming previous reports using recombinant S1 or S-RBD subunit vaccines (28,32,(36)(37)(38)(39).…”
Section: Priming Of S-rbd-specific Antibody Responses In Young Mice B...supporting
confidence: 90%
See 1 more Smart Citation
“…Irrespective of the antigen conformation, the S-specific antibodies developed in different DNA-(pCI/S, pCI/S2-P, pCI/S6-P DTM ) or proteinimmunized (S, S2-P, S6-P DTM ) young mice efficiently suppressed S-mediated cell entry of pseudovirus particles (Figure 3B). This showed that both trimeric and monomeric S proteins elicited substantial pseudovirus-neutralizing antibodies in young mice, confirming previous reports using recombinant S1 or S-RBD subunit vaccines (28,32,(36)(37)(38)(39).…”
Section: Priming Of S-rbd-specific Antibody Responses In Young Mice B...supporting
confidence: 90%
“…In contrast, it was well established that genetically engineered TM-deficient S proteins of coronaviruses and SARS-CoV-2 were secreted into the cell culture supernatant, expressed at higher levels than full-length S proteins, but these monomeric proteins failed to assemble into trimeric structures unless modified with an artificial trimerization domain (24,(28)(29)(30)(31)(32)(33)(34)(35). It is not clear to what extent conformational trimeric S-structures induce S-and/or S-RBD-specific neutralizing antibody responses, since neutralizing antibodies could also be primed by monomeric S-RBD-or S1-subunit antigens (32,(36)(37)(38)(39). The S-specific antibody response thus might also be directed against conformation-independent domains within the S-RBD or against domains that do not cover the S-RBD at position S 319-541 (24).…”
Section: Introductionmentioning
confidence: 99%
“…In a 6 months period, the first collaborative article condensing part of the work on the characterization of the RBD of SARS-CoV-2 produced by HEK-293T human cells and in Pichia Pastoris was sent for publication ( 6 ). During this period, we also supplied high quality RBD antigen (through University MTAs) to 9 different institutions across Argentina for use in their basic and applied research projects ( 9 , 10 ). 7 In the meantime, members of the Consortium took part in several outreach activities where not only general COVID-19 information was shared but also results and work perspectives ( 11 ).…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, SARS-CoV-2 spike trimer conjugated with a unique adjuvant LP-GMP was designed, consisting of TLR2 and STING agonists by generating potent specific IgG, IgA, and memory T cells (tissue-resident memory T-cells) in both lungs and nasal mucosa in human ACE-2 transgenic (K18-hACE) mice [95]. Another promising STING agonist (c-di-AMP)-based vaccine was designed using monomeric RBD along with CDG SF , displaying an enhanced immunogenicity with appreciated neutralizing antibody and Th1-biased immune responses when compared with aluminum hydroxide (Al (OH) 3) [96,97]. Alternatively, a ternary adjuvant vaccine, comprising of Alum + c-GAMP + poly (I: C) with STING agonist 3, 3′-c-GAMP (c-GAMP) and TLR3 agonist poly (I: C) combined with S1 protein was introduced.…”
Section: Advances In Sting Agonist-adjuvant Vaccines Against Covid-19mentioning
confidence: 99%